Public Perceptions of Calf Disbudding Techniques Used on Texas Farms - Andrea D. Calix; Pablo Lamino; Howard Rodríguez-Mori; Arlene Garcia; Elpida Artemiou (Animals)
This study investigates public perceptions in Texas regarding two common calf disbudding methods used in dairy farming: caustic paste and hot iron. With growing consumer interest in humane animal treatment, understanding the preferences for these methods provides insights into public expectations of welfare in agricultural practices. The study utilized an online survey distributed to Texas residents via the Centiment research platform, assessing preferences, demographic influences, and the impact of scientific information on perceptions. Results, from 511 participants, indicated a stronger preference for caustic paste, especially among women and participants with higher education levels, while hot iron was favored more by men. Dietary habits, such as seafood and cheese consumption, also influenced preferences, with higher consumption linked to a preference for caustic paste. Viewing images of the disbudding techniques affected the willingness to purchase, consume, and serve beef, with hot iron prompting a greater negative response. The findings suggest that public knowledge and awareness can significantly impact perceptions surrounding animal welfare practices and that education could play a critical role in aligning consumer preferences with humane agricultural practices. These insights are valuable for the dairy industry, informing practices that are more aligned with public expectations and supporting the promotion of welfare-oriented disbudding methods.